Unfractionated Heparin Improves the Intestinal Microcirculation in a Canine Septic Shock Model - Heng Zhang; Yini Sun; Xin An; Xiaochun Ma (Hindawi Limited, 2021)
Background. Alterations of microcirculation are associated with organ hypoperfusion and high mortality in septic shock. This study is aimed at investigating the effects of unfractionated heparin (UFH) on intestinal microcirculatory perfusion and systemic circulation in a septic shock model. Methods. Twenty-four beagle dogs were randomly allocated into four groups: (a) sham group: healthy controls, (b) shock group: septic shock induced by Escherichia coli, (c) basic therapy group: septic shock animals treated with antibiotics and 10 ml/kg/h saline, and (d) heparin group: septic shock animals treated with basic therapy plus UFH. Hemodynamic variables were measured within 24 h after E. coli administration. The intestinal microcirculation was simultaneously investigated with a sidestream dark-field imaging technique. Additionally, the function of vital organs was evaluated at 12 h postadministration (T12). Results. E. coli induced a progressive septic shock in which the mean arterial pressure (MAP) decreased and lactate levels sharply increased, accompanied by deteriorated microvessel perfusion. While basic therapy partially improved the microvascular flow index and the perfused microvessel density in the jejunal villi, UFH significantly restored major microcirculation variables at T12. Physiological variables, including MAP, urine output, and lactate levels, were improved by UFH, whereas some hemodynamic indices were not affected by UFH. With respect to organ function, UFH increased the platelet count and decreased the creatinine level. Conclusions. UFH improves microcirculatory perfusion of the small intestine independently of the changes in systemic hemodynamic variables in a canine model of septic shock, thereby improving coagulation and renal function.